2019
DOI: 10.32098/mltj.03.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered augmentation of a rotator cuff tendon using a reconstituted collagen scaffold: a histological evaluation in sheep

Abstract: To determine if an absorbable collagen scaffold of high porosity would allow rapid tissue ingrowth and permit the functional maturation and alignment of tendon-like tissue, scaffolds were sutured to the superficial surface of the infraspinatus tendons of adult sheep. Histology demonstrated complete ingrowth with fibrovascular tissue by 6 weeks and by 12 weeks the scaffold had induced the formation of a layer of dense, regularly-oriented collagenous tissue which significantly increased the thickness of the nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 14 publications
4
56
0
1
Order By: Relevance
“…The reconstituted collagen scaffolds were made from highly-purified, type I collagen from bovine tendons using proprietary methods (Collagen Matrix, Inc., Oakland, New Jersey) 18 . The collagen fibers were processed to create a highly oriented and highly porous (85-90% porosity) collagen scaffold with a DNA content of less than 50 ng/mg 18 . The scaffolds were freeze-dried after processing and rehydrated at the time of surgery 18 .…”
Section: Collagen Scaffoldmentioning
confidence: 99%
“…The reconstituted collagen scaffolds were made from highly-purified, type I collagen from bovine tendons using proprietary methods (Collagen Matrix, Inc., Oakland, New Jersey) 18 . The collagen fibers were processed to create a highly oriented and highly porous (85-90% porosity) collagen scaffold with a DNA content of less than 50 ng/mg 18 . The scaffolds were freeze-dried after processing and rehydrated at the time of surgery 18 .…”
Section: Collagen Scaffoldmentioning
confidence: 99%
“…Several studies have reported that indirect connection, mostly consisting of Sharpey's-like fibers, was observed in the healing process of different tendon-bone models. [7][8][9] Nevertheless, this indirect connection with poorly organized fibers between the tendon and the bone was far from the native structure and had insufficient pullout strength. As a result, the inferior mechanical and biochemical properties of the repaired tissue could increase the risk of reinjury and continued disability.…”
Section: Introductionmentioning
confidence: 99%
“…Following the animal experiments and the finite element studies, the porous collagen implant was used in humans to treat partial thickness cuff tears, and also as an augment to the treatment of full thickness cuff tears (11,24). Subsequent published tissue retrieval studies confirmed that the histological changes seen in human specimens corresponded precisely with the findings of the sheep study of Van Kampen et al (23,25). Use of the collagen implant as an alternative to completion of the tear and performing a repair has the advantage of requiring only 1 week in a sling and return to unrestricted activities at 6 weeks postoperative.…”
Section: Discussionmentioning
confidence: 94%
“…Finite element analysis suggests that the addition of 2 mm of tissue to the bursal surface of a partial thickness tear can significantly decrease peak intra-tendinous strain by 40% in articular-side and 47% in bursal-side partial-thickness tears (11). Sheep studies by Van Kampen et al have shown that placing a highly-porous collagen implant on the bursal surface of the infraspinatus tendon would induce the formation of a fibrovascular tissue resem- bling tendon and result in a significant and consistent thickening of the infraspinatus tendon (23). Following the animal experiments and the finite element studies, the porous collagen implant was used in humans to treat partial thickness cuff tears, and also as an augment to the treatment of full thickness cuff tears (11,24).…”
Section: Discussionmentioning
confidence: 99%